Increasing Fourth Form Students’ Achievement Results and Motivation for Learning the English Vocabulary: The Impact of Quizlet - Streckienė, Evelina; Bukšnytė-Marmienė, Loreta (Pedagogika, 2023)
The ability to communicate in a variety of languages is a valuable competence in the dynamic and diverse world. However, primary school students are not sufficiently motivated to learn English vocabulary. The research was carried out in order to assess the impact of the use of Quizlet on achievement results and motivation of the fourth form students to learn the English vocabulary. The review of scientific resources deals with the possible impact of Quizlet on students’ achievement results and motivation. The impact on achievement results is disputable among researchers. However, it was determined that Quizlet has a positive influence on the learning motivation and engagement of students in terms of time spent and autonomy as well as their attitude towards learning the English vocabulary and emotions experienced. The empirical study compares the initial situation with the situation after the introduction and use of Quizlet. Students’ achievement results were measured by means of diagnostic tests, and data on students’ motivation were collected by means of survey (interview) (for measuring engagement) and semantic differential based survey (for measuring attitude towards learning and emotions). After using Quizlet for five weeks, students’ learning motivation increased: an increase in students’ engagement and a positive change of students’ attitude and emotions were observed, although the innovation had no significant influence on achievement results.